Traversing the boundaries in landscapes of practice: A mixed methods study of interprofessional education centered on inpatients in an acute hospital setting - Nora McCarthy; Amy Slattery; Jennifer Daly; Helen Hynes (Springer, 2024)
Abstract Healthcare requires practitioners to successfully negotiate boundaries between communities of practice (CoP) in a clinical landscape of practice (LoP), with development of interprofessional identity important in promoting successful interprofessional collaboration. Interprofessional education (IPE) centered around acute hospital inpatients offers a potential pathway to encourage boundary negotiation and interprofessional identity development. This study aimed to explore interprofessional student teams and their interactions with patients in an acute hospital setting, while investigating if such interactions encouraged interprofessional collaboration and the development of an interprofessional identity. Pivoting around acute hospital inpatients, four interprofessional workshops occurred involving senior medicine, nursing and physiotherapy students. We utilized a concurrent mixed methods design, with qualitative predominating. Qualitative reflexive thematic analysis of post-workshop semi-structured focus groups was supported by quantitative investigation using a validated pre-test post-test international socialisation and valuing scale. Using the landscapes of practice theory lens, we noted that the central role of acute hospital inpatients in the IPE workshops enabled healthcare students to develop knowledgeability of the clinical LoP, in line with the three modes of identification of LoP, namely Engagement, Imagination and Alignment. Following the IPE workshops, where acute inpatients played the pivotal role, students demonstrated a statistically significant increase in interprofessional collaborative practice in terms of the overall interprofessional socialisation and valuing scale and its subscales of value, ability, and comfort in working with each other. Our findings indicate that IPE centered around acute hospital inpatients is a beneficial and effective way to successfully implement IPE in the undergraduate curriculum.